# Question: The joint density function of X and Y is given

The joint density function of X and Y is given by

f (x, y) = xe−x(y+1) x > 0, y > 0

(a) Find the conditional density of X, given Y = y, and that of Y, given X = x.

(b) Find the density function of Z = XY.

f (x, y) = xe−x(y+1) x > 0, y > 0

(a) Find the conditional density of X, given Y = y, and that of Y, given X = x.

(b) Find the density function of Z = XY.

**View Solution:**## Answer to relevant Questions

The joint density of X and Y is f (x, y) = c(x2 − y2)e−x 0 ≤ x < ∞, −x ≤ y ≤ x Find the conditional distribution of Y, given X = x. Repeat Problem 3a when the ball selected is replaced in the urn before the next selection. Problem 3 In Problem 2, suppose that the white balls are numbered, and let Yi equal 1 if the ith white ball is selected and 0 ...If X1 and X2 are independent exponential random variables, each having parameter λ, find the joint density function of Y1 = X1 + X2 and Y2 = eX1. In Example 5c we computed the conditional density of a success probability for a sequence of trials when the first n + m trials resulted in n successes. Would the conditional density change if we specified which n of these ...Suppose that W, the amount of moisture in the air on a given day, is a gamma random variable with parameters (t, β). That is, its density is f(w) = βe−βw(βw)t−1 / Γ(t), w > 0. Suppose also that given that W = w, the ...Post your question